An Assessment Of Water Quality For Ain Al-Fawara In Tolmeitha, Libya Using Physiochemical And Microbial Parameters (Al-Mukhtar Journal of Basic Sciences, 2026)
Ain Alfawarra is located in Tolmeitha in the northeastern coast of Libya and its water is utilized locally for livestock consumption. This study aimed to assess water contamination in this natural, surface water source. Chemical and biological analysis has been performed to determine the level of pollution at a private, certified laboratory. Chemical analysis include qualitative analysis of cations and spectrophotometric techniques. Microbial analysis, however, was performed using traditional cultivation techniques. Even though, this Ain has not been used for human consumption, its contamination still affects public health indirectly through probable leaking into ground water or spreading waterborne diseases among animals and through insects. Chemical analysis has shown high lead levels 0.028mg/L, exceeding the WHO permissible limit of 0.01mg/L. Biological analysis has shown high bacteria counts (total bacteria:>2419.6 CFU/mL; total coliform: 1100 CFU/100ml; E.coli:1100 CFU/100ml; Fungi:>300 CFU/ml; S.faecalis: 29.1 CFU/100 mL, all exceeding international safety limits. The findings of this study suggested restricting this area for both animal and human consumption, and then manage a hygienic plan. This area needs to be monitored biologically and chemically and then treated.